Risk Management for Rate of Return Using Stress Testing Techniques in Compliance with the Islamic Financial Services Board (IFSB) Standards – A Case Study of Al Rajhi Bank- (Journal of Economic Additions, 2025)
This study focuses on analyzing the effectiveness of stress testing in measuring rate-of-return risks and its pivotal role in the Islamic banking sector, It explains how rate-of-return stress testing techniques are used within risk management frameworks according to the Islamic Financial Services Board (IFSB), A financial shock scenario was applied to Al Rajhi Bank as a case study, based on the data of its 2024 annual financial report, integrating the relevant variables into a single framework, The results revealed that Al Rajhi Bank exhibited high financial resilience in facing the shock scenario, recording only a slight decline but recovering quickly due to the bank's strong financial position.  Keywords: Risk management, rate of return, stress tests.Jel Classification Codes: G21, G32